2022
DOI: 10.55643/fcaptp.4.45.2022.3835
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and Innovations in the Management of Economic Systems: Ukrainian Experience, Responses to Contemporary Challenges

Abstract: Ukraine is currently facing an acute issue of economic recovery, as the country seeks to emerge from the devastating effects of the global pandemic and level out and overcome the negative impact of the intensification of military operations on its territory. Given the above, the purpose of the article is to study Ukraine's experience in strategic management of economic systems, taking into account the existing experience and accumulated practices, as well as to substantiate proposals for the development and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It was also concluded that the Compulsory State Social Health Insurance Fund was also improved for healthcare delivery during the pandemic. A competitive market model is being studied for future healthcare improvements in Ukraine and for this purpose Lohinova and Marushchak examined the pros and cons of market-based healthcare in Ukraine [36]. While another study examined healthcare system in the United Kingdom where health care is entirely financed and provided by the government to all citizens.…”
Section: Discussionmentioning
confidence: 99%
“…It was also concluded that the Compulsory State Social Health Insurance Fund was also improved for healthcare delivery during the pandemic. A competitive market model is being studied for future healthcare improvements in Ukraine and for this purpose Lohinova and Marushchak examined the pros and cons of market-based healthcare in Ukraine [36]. While another study examined healthcare system in the United Kingdom where health care is entirely financed and provided by the government to all citizens.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing strategic management and allocating resources is crucial for achieving goals. Promoting enterprise management innovation and forming a management system with enterprise characteristics enhances independent innovation, building sustainable enterprises, and meeting scientific and technological needs (Oneshko et al, 2022). Chinese companies adopting innovative management strategies have made significant achievements, contributing to technological progress and economic growth (Deng & Shi, 2023) Many enterprises lack a clear understanding of innovation management, leading to low strategic management ability and limited innovation-driving role (Laphet et al, 2023).…”
Section: Introductionmentioning
confidence: 99%